Of children : an introduction to child development - Lefrançois, Guy R. (Belmont, Calif : Wadsworth Pub. Co., 1991)
As in previous editions, this book approaches the study of child development from an inside/outside perspective, looking at children from an abstract or research-based point of view as well as from a personal or experiential perspective
Includes bibliographical references and indexes.
Keywords: Child development